MOTIVASI PETANI DALAM BERUSAHA TANI NILAM DI DESA PUUNGGAPU KECAMATAN ANDOOLO KABUPATEN KONAWE SELATAN - Muhammad Amin; Yani Taufik; Suriana Suriana (Universitas Halu Oleo, 2023)
The price of patchouli plants has fluctuated considerably from 2017 to 2022, but currently remains resilient at Rp.450,000/kg and is expected to continue increasing. This study aims to examine the types of motivation and the income of farmers who cultivate patchouli in Puunggapu Village. The population of this study includes all 20 patchouli farmers in Puunggapu Village. The study sample consisted of 20 farmers selected through the census method. Data were collected using observation, interviews, and documentation with an interview guide. Descriptive analysis was employed to determine farmers' motivation for cultivating patchouli and to calculate their income level. The study revealed that farmers in Puunggapu Village were motivated to cultivate patchouli due to intrinsic and extrinsic factors. Extrinsic motivation was not mentioned in the original text. Intrinsic motivation was driven by the desire to increase income, fulfill life needs, gain experience in farming, and the ease of cultivating patchouli. Extrinsic motivations for planting patchouli in Puunggapu Village include the high price of patchouli oil, the prevalence of patchouli farming among local farmers, the low maintenance required for patchouli plants, and the availability of markets to sell the resulting patchouli oil. On average, farmers in the village earn IDR 8,455,000 per growing season (6 months) from patchouli farming.